DEMPSTER SHAFER'S ROLE IN THE EXPERT SYSTEM IN DIAGNOSING PET SKIN DISEASES - Gita Malinda; Andi Farmadi; Muliadi Aziz (Lambung Mangkurat University, 2019)
Cats are pets that are very close to humans. Infectious pet diseases can sometimes spread quickly and can be fatal, both in animals and humans. For early prevention, the pet disease must be immediately known which in this case is a cat skin disease. To find out the diagnosis of cat skin disease using the Dempster-Shafer method. So that the results obtained the strongest confidence value of cat skin disease A1, A3, A4 which is equal to 0.48, which was obtained from three existing symptoms, namely wet dry crust, moist inner moist ear and frequent scratching.Keywords: Cats, Expert System, Dempster Shafer.Kucing merupakan hewan peliharaan yang sangat dekat dengan manusia.. Penyakit hewan peliharaan yang menular terkadang dapat menyebar secara cepat dan dapat berakibat fatal, baik pada hewan dan manusia. Untuk pencegahan dini maka penyakit hewan peliharaan tersebut harus segera diketahui yang dalam kasus ini adalah penyakit kulit kucing. Untuk mengetahui diagnose penyakit kulit kucing tersebut menggunakan metode dempster-shafer. Sehingga memproleh hasil Nilai keyakinan paling kuat terhadap penyakit kulit kucing A1,A3,A4 yaitu sebesar 0,48, yang didapat dari tiga gejala yang ada yaitu kerak kering basah, bagian dalam telinga basah lembab dan sering menggaruk.Kata kunci: Kucing, Sistem Pakar, Dempster Shafer.